Association between monocyte-to-lymphocyte ratio and cardiovascular diseases: insights from NHANES data - Xiaowan Li; Liyan Zhang; Yingying Du; Yiru Shen; Yuanzhi Gong; Junjie Wang; Juan Zhou; Sheng Wang (Diabetology & Metabolic Syndrome)
Abstract Background This study intends to examine any possible correlation between monocyte-to-lymphocyte ratio (MLR) and cardiovascular diseases (CVD). Methods Data from the 1999–2020 National Health and Nutrition Examination Survey (NHANES) in the USA were analyzed. Heart attacks, angina pectoris, congestive heart failure (CHF), coronary heart disease (CHD), and stroke were all covered by CVD. The independent relationships between these cardiovascular events and MLR levels, as well as other inflammatory indices (system inflammation response index (SIRI), aggregate index of systemic inflammation (AISI), and C-reactive protein-to-albumin ratio (CAR)), were investigated. Furthermore, interaction tests and subgroup analysis were performed. Diagnostic capacities were also predicted and compared using receiver operating characteristic (ROC) curves. Results Males made up 49.63% of the 46,289 people who were recruited in this study. The prevalence of CVD and its events were as follows: CHF at 2.99%, CHD at 3.72%, angina pectoris at 2.57%, heart attacks at 3.94%, and stroke at 3.48%, with CVD itself at 7.98%. MLR and CVD were positively correlated. Specifically, smooth curve fittings also found a non-linear relationship between MLR and CVD. Moreover, higher MLR levels were linked to increased rates of CHF, CHD, and strokes. SIRI was also found to have a positive correlation with CVD. MLR outperformed other inflammatory indices (SIRI, AISI, and CAR) in terms of discriminative capacity and accuracy in predicting CVD, CHF, CHD, angina pectoris, heart attack, and stroke, according to ROC analysis. Conclusions Compared with other inflammatory indicators (SIRI, AISI, and CAR), MLR appears to be a better inflammatory index for predicting CVD, CHF, CHD, angina pectoris, heart attack, and stroke. American adults with elevated MLR and SIRI should be aware of the possible harm caused by CVD. Causal inference is, however, limited by the cross-sectional design and dependence on self-reported data. Further longitudinal studies are needed to validate these findings.